History, memory and migration : perceptions of the past and the politics of incorporation - Kleist, J. Olaf, 1975-; Glynn, Irial, 1979- (Palgrave Macmillan memory studies., 2012)
As the growing diversity of societies is recognised as both an asset and a challenge, academia has been forced to re-evaluate some of its basic assumptions about migrant incorporation and social memories. However, scholars have rarely combined Migration Studies and Memory Studies to consider how perceptions of the past affect the incorporation of immigrants in their host societies. The authors in this volume merge the extensive knowledge and relevant findings produced in both fields. They demonstrate, through a series of empirical studies from Europe, North America, Australia, Asia and the Middle East, how various actors have referenced diverse conceptions of their local, regional and national pasts to include and exclude immigrants from receiving societies. By focusing on how the presentation of a certain past relates to the immigration present, the book aims to examine the relationship between the politics of memory and the incorporation of immigrants.